Communication Satisfaction and Citizenship Behavior: A Mediated Model for Public Sector Transformation - Lestari, Putri Ayu (Indonesian Scientific Publication, 2025)
His study examines the effect of Organizational Communication Satisfaction (OCS) on Organizational Citizenship Behavior (OCB) in Indonesian State-Owned Enterprises (SOEs), with Employee Engagement (EE) and Employer Branding (EB) as mediators. A cross-sectional survey of 336 employees was conducted using validated Likert-scale instruments. Data were analyzed with Partial Least Squares Structural Equation Modeling (PLS-SEM), ensuring reliability and validity. Results show that OCS significantly predicts OCB (β = 0.31, p < 0.01). Both EE (β = 0.12, p = 0.017) and EB (β = 0.10, p = 0.024) partially mediate this relationship. These findings highlight that communication satisfaction influences behavior through emotional and symbolic mechanisms. This study concludes that effective internal communication is a strategic resource for SOEs, fostering trust, engagement, and organizational resilience. Practical implications emphasize participatory and culturally sensitive communication strategies, while theoretically this research extends the OCS–OCB literature by integrating dual mediators in a public sector context.